Towards a global polity - Ougaard, Morten; Higgott, Richard A.; University of Warwick. Centre for the Study of Globalisation and Regionalisation; Economic and Social Research Council (Great Britain) (London ; New York : Routledge, 2002)
This collection examines the political aspects of globalization which may be creating the much-feared 'One World Government'. The contributors discuss the core issues in the debate about global governance: national sovereignty, law, public management, networks, economic governance, institutions, Europe and good governance.
"Centre for the Study of Globalisation and Regionalisation; E.S.R.C., Economic & Social Research Council."
Includes bibliographical references (p. [227]-256) and index.
oif 21/08/15
Loan
Keywords: International relations; Globalization